Desempenho de híbridos de milho safrinha em função de fontes de ureia na adubação de cobertura - WIEST, GABRIEL; PEREIRA, CASSIANO SPAZIANI; FIORINI, IVAN VILELA ANDRADE; SCHOFFEN, MATEUS EMANUEL; PEREIRA, HELCIO DUARTE; SILVA, ADRIANO ALVES DA (Revista Agrogeoambiental, 2021)
Nitrogen is the most required element by the maize crop and suffers the greatest losses due to its inappropriate management, mainly when the urea is used as a source of nitrogen. The objective of this work was to evaluate the efficiency of urea sources, with or without urease inhibitor, in sidedress fertilization of commercial single-cross in off-season in Sinop/MT. The experimental design was completely randomized blocks, in factorial scheme 3 x 5, with 3 replications. The first factorwas three side-dress fertilization: witness (without fertilizer); fertilization with 250 kg ha-1 of urea and fertilization with 250 kg ha-1 of urea in the presence of urease inhibitor (UREMAX®) NBPT. The second factor was five single-crosses: 2B433, DKB255, DKB335, NS45, and SYN522. Vegetative development and yield characteristics were evaluated. The Nitrogen sources did not affect the plant height, stem diameter, and foliar area index, only the chlorophyll content in the leaves. For the yield components, there is an effect of fertilization on the number of grain rows and grain yield. The singlecrosses differ among them in vegetative development and yield characteristics. The Nitrogen in sidedress, in the conditions of this study, using the urea with urease inhibitor, increased the fertilization efficiency and raised the grain yield. The single-crosses DKB 255, 2B433, and SYN 522, with the treatment based on UREMAX®, reached the highest yield.